Quiet time equatorial mass density distribution derived from AMPTE/CCE and GOES using the magnetoseismology technique. Issue 10 (3rd October 2013) - Min, Kyungguk; Bortnik, Jacob; Denton, Richard E.; Takahashi, Kazue; Lee, Jeongwoo; Singer, Howard J.
<x xml:space="preserve">Abstract</x> [1] An inversion technique for estimating the properties of the magnetospheric plasma from the harmonic frequencies of the toroidal standing Alfvén waves has been used to derive the global equatorial mass density covering radial distances from 4 to 9 Earth radii (RE), within the local time sector spanning from 0300 to 1900 h. This broad range of L shell extending to the outer magnetosphere allows us to examine the local time and radial dependence of the quiet time equatorial mass density during solar minimum and thereby construct a global distribution of the equatorial mass density. The toroidal Alfvén waves were detected with magnetometers on the Active Magnetospheric Particle Tracer Explorers (AMPTE)/Charge Composition Explorer (CCE) during the nearly 5 year interval from August 1984 to January 1989 and on the Geostationary Operational Environmental Satellites (GOES) (10, 11, and 12) for 2 years from 2007 to 2008, both of which were operating during solar minimum years. The derived equatorial mass density, ρeq, at geosynchronous orbit (GEO) monotonically increases with increasing magnetic local time (MLT) from the nightside toward the dusk sector. At other radial distances, ρeq has the same MLT variation as that of GEO, while the magnitude logarithmically decreases with increasing L value. An investigation of the Dst and Kp dependence shows that the median value of ρeq varies little in the daytime sector during moderately disturbed times, which agrees with previous studies. ρeq calculated from the F10.7 dependent empirical model shows good agreement with that of CCE but overestimates that of GOES probably due to the extreme solar cycle minimum in years 2007–2008.